Learning network and corporate university in the public sector: An integrative review - Souto, Breno Jaime Amaral; Neves, Marta Silva; Loth, Adriana Falcão; Alves, Ernestina da Silva; Freire, Patricia de Sá (Seven Editora, 2023)
The Knowledge Society passes through a complex, competitive and dynamic world portrayed in technology, globalization, reconfiguration of productive practices, and work flexibility, among other aspects. For survival and development, organizations started to work in networks with a view to co-producing more effective results. However, not all networks produce the expected results. The authors of this study identified in the literature the construct "learning networks", defined as network learning by Louise Knight (2002).  5 stages of corporate maturity of inter-organizational networks, and to evolve between them, multilevel learning, proposed by corporate universities, is necessary. In this sense, corporate universities will contribute to the improvement of multiple actors, stimulating involvement, involvement, learning, production of knowledge, meanings of products, results, and businesses. The article aims to identify a public knowledge gap about the relationship between corporate universities and learning networks for their application in the sector. An exploratory-bibliographic study was carried out based on an integrative review and content analysis. few studies on the relationship between the constructs of corporate universities and learning networks and the application in the sector of collaborative networks and public knowledge, for the creation and learning of organizational learning. DOI:https://doi.org/10.56238/alookdevelopv1-031